2021
DOI: 10.1038/s41598-021-00565-3
|View full text |Cite
|
Sign up to set email alerts
|

The genome of the diatom Chaetoceros tenuissimus carries an ancient integrated fragment of an extant virus

Abstract: Diatoms are one of the most prominent oceanic primary producers and are now recognized to be distributed throughout the world. They maintain their population despite predators, infections, and unfavourable environmental conditions. One of the smallest diatoms, Chaetoceros tenuissimus, can coexist with infectious viruses during blooms. To further understand this relationship, we sequenced the C. tenuissimus strain NIES-3715 genome. A gene fragment of a replication-associated gene from the infectious ssDNA virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The genomes we considered for the present study have been generated from the Tara Oceans metagenomic reads and displayed the same magnitude in size, number of protein-coding genes and G+C content as the newly published Chaetoceros tenuissimus genome (Hongo et al 2021), pointing out the accuracy of the MAG reconstruction methods. Several studies have investigated the link between genome size compared to cell morphology and metabolism and have found that both cell size and growth rate are, respectively, proportional and inversely proportional to genome size (Williams 1964; Holm-Hansen 1969; Shuter et al 1983; Veldhuis et al 1997; Cavalier-Smith 2005; Von Dassow et al 2008).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The genomes we considered for the present study have been generated from the Tara Oceans metagenomic reads and displayed the same magnitude in size, number of protein-coding genes and G+C content as the newly published Chaetoceros tenuissimus genome (Hongo et al 2021), pointing out the accuracy of the MAG reconstruction methods. Several studies have investigated the link between genome size compared to cell morphology and metabolism and have found that both cell size and growth rate are, respectively, proportional and inversely proportional to genome size (Williams 1964; Holm-Hansen 1969; Shuter et al 1983; Veldhuis et al 1997; Cavalier-Smith 2005; Von Dassow et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…For this, we selected the MAGs that were present in at least three different stations or depths and with a variance superior to zero, namely MAGs ARC_116, ARC_217 and SOC_37, all of them having populations in the Arctic Ocean. Pairwise-FST values between the MAG populations were modelled depending on a range of environmental parameters and Euclidean distance by applying a linear mixed model (LMM), as described in Laso-Jadart et al (2021), to perform a variance partitioning analysis. The fixed part of the unexplained variance was below 10% for the three analyses, and was therefore considered negligible.…”
Section: Global Population Structure Among Arctic Ocean Regionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reference diatom genomes for P. tricornutum CCAP 1055 and T. pseudonana CCMP 1335 were also considered to provide a comparison with the Chaetoceros MAGs and were both retrieved from the Joint Genome Institute [16,17]. The genome of Chatoceros tenuissimus NIES-3715 was retrieved from the DDBJ repository (https://www.ddbj.nig.ac.jp) [81]. Information about their completion level, gene length, and percentage of G+C were obtained with the aforementioned methods, except for C. tenuissimus for which the genes were not available.…”
Section: Genomic Resourcesmentioning
confidence: 99%